UJI AKTIVITAS ANTIOKSIDAN ETANOL BUAH TIN (Ficus carica) DENGAN METODE DPPH DAN FRAP - Rachmat Faisal Syamsu; Mochammad Erwin Rachman (As-Syifaa Jurnal Farmasi, 2023)
Indonesia as a developing country has limitations in overcoming health problems. Based on the 2018 National Basic Health Research (Riskesdas), the prevalence of degenerative diseases is increasing. The main cause of death was stroke (15.4%) followed by hypertension, diabetes mellitus, and tumors. One of the causes of this degenerative disease is oxidative stress, namely the large number of oxidants in the body through an oxidation process. Antioxidants are compounds that prevent or postpone oxidation reaction of a molecule by inhibiting initiation or propagation process of the chain oxidation reaction The chemical structure of antioxidants, free radical sources, and physico-chemical properties of different sample preparations can provide various antioxidant activity test results. Therefore, a selective antioxidant activity analysis method is needed for a certain type of sample. The purpose of this study was to test the antioxidant activity of the ethanol extract of fig fruit using the DPPH and FRAP. Methods This research was conducted using the antioxidant activity test method DPPH and FRAP. Based on the research results of antioxidant activity using the DPPH method, the IC50 value of the ethanol extract of fig fruit was 121.74 μg/mL and the FRAP method obtained a value of 11.11 mgAAE/g extract